Gp35/50 mucin molecules of Trypanosoma cruzi metacyclic forms that mediate host cell invasion interact with annexin A2 - Thiago Souza Onofre; Leonardo Loch; João Paulo Ferreira Rodrigues; Silene Macedo; Nobuko Yoshida (Public Library of Science (PLoS), 2022)
Host cell invasion is a critical step for infection by Trypanosoma cruzi, the agent of Chagas disease. In natural infection, T. cruzi metacyclic trypomastigote (MT) forms establish the first interaction with host cells. The gp35/50 mucin molecules expressed in MT have been implicated in cell invasion process, but the mechanisms involved are not well understood. We performed a series of experiments to elucidate the mode of gp35/50-mediated MT internalization. Comparing two parasite strains from genetically divergent groups, G strain (TcI) and CL strain (TcVI), expressing variant forms of mucins, we demonstrated that G strain mucins participate in MT invasion. Only G strain-derived mucins bound to HeLa cells in a receptor-dependent manner and significantly inhibited G strain MT invasion. CL strain MT internalization was not affected by mucins from either strain. HeLa cell invasion by G strain MT was associated with actin recruitment and did not rely on lysosome mobilization. To examine the involvement of annexin A2, which plays a role in actin dynamic, annexin A2-depleted HeLa cells were generated. Annexin A2-deficient cell lines were significantly more resistant than wild type controls to G strain MT invasion. In a co-immunoprecipitation assay, to check whether annexin A2 might be the receptor for mucins, protein A/G magnetic beads crosslinked with monoclonal antibody to G strain mucins were incubated with detergent extracts of MT and HeLa cells. Binding of gp35/50 mucins to annexin A2 was detected. Both G strain MT and purified mucins induced focal adhesion kinase activation in HeLa cells. By confocal immunofluorescence microscopy, colocalization of invading G strain MT with clathrin was visualized. Inhibition of clathrin-coated vesicle formation reduced parasite internalization. Taken together, our data indicate that gp35/50-mediated MT invasion is accomplished through interaction with host cell annexin A2 and clathrin-dependent endocytosis. Author summary Host cell invasion by Trypanosoma cruzi, the agent of Chagas disease, is critical for the establishment of infection. Metacyclic trypomastigote (MT) forms are responsible for the initial T. cruzi-host cell interaction. Mucin molecules expressed on MT surface have been implicated in target cell invasion process, but the underlying mechanism are not fully understood. In this study, we aimed at elucidating the mode of mucin-mediated MT internalization. We found that requirement of mucins for MT invasion is T. cruzi strain-dependent. Experiments with G strain MTs, which rely on mucins and on target cell actin for internalization, revealed that mucin molecules bind to annexin A2, a protein that plays a role in actin dynamic. Annexin A2-deficient cell lines were generated and found to be significantly more resistant than wild type controls to MT invasion. Both MT and purified mucins induced focal adhesion kinase activation in host cells. By confocal immunofluorescence microscopy, invading MT was found to colocalize with clathrin, a protein that plays a role in endocytosis. Inhibition of clathrin-coated vesicle formation reduced parasite internalization. From these data we infer that mucin-mediated MT invasion is accomplished through interaction with host cell annexin A2 and clathrin-dependent endocytosis.